EVALUATING ROUTINES IN TRAMPOLINE GYMNASTICS - Thomas Heinen; Freya Krepela (Science of Gymnastics Journal)
In trampoline gymnastics, judges’ task is to evaluate a particular routine based on the evaluation of overall degree of difficulty, overall skill execution, and the measurement of time of flight duration. The aim of this study was to investigate differences in the three judgment variables between gymnast’s age, gymnast’s gender, year of competition, and in relation to the final competition standings in trampoline gymnastics. N = 279 datasets from the World Championships and World Age Group Competitions of the years 2011, 2013, 2014, and 2015 served as a database for this study. Results revealed that the judgment variables varied as a function of gymnasts’ age, gymnasts’ gender, and year of competition. For example, male gymnasts exhibited higher difficulty scores, slightly higher execution scores, higher time of flight scores, and higher total scores as compared to their female counterparts. A similar pattern of results was found when comparing senior gymnasts to gymnasts from younger age groups. Furthermore, all three judgment variables contributed to final competition standings. Difficulty score showed in average a larger contribution while execution score showed in average a tendency to a slightly smaller contribution for male gymnasts, as compared to female gymnasts. From the viewpoint of an individual gymnast, it is concluded that execution score of a routine should be maximized, while time-of-flight score should be optimized given the difficulty that a gymnast is able to present in a particular routine, thereby guaranteeing a safe and deduction-free skill performance.